A polyether aspartic acid ester containing aldehyde (ketone) imine and its application in wind turbine blade coating

By using trifunctional polyether type aspartate esters to synthesize aldehyde (ketone) imine polyether type aspartate, combined with other resins and curing agents, a two-component asparagus polyurea coating was formed, which solved the problem of insufficient performance of existing wind power blade leading edge protection coatings in resisting wind sand and rain fog corrosion, and achieved high-performance coatings and good construction performance.

CN117887063BActive Publication Date: 2025-03-25V ABC PAINTS MFG JIANGXI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410026151.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-09
Publication Date
2025-03-25
Estimated Expiration
2044-01-09

AI Technical Summary

Technical Problem

The existing wind power blade leading edge protective coatings have insufficient performance in resisting wind sand and rain fog corrosion, and the process is complicated, making it difficult to achieve a uniform and smooth protective coating.

Method used

The trifunctional polyether type aspartate is used as the resin component, and the primary amino group is blocked by aldehyde (ketone) compounds and Michael addition reaction is carried out to synthesize aldehyde (ketone) imine polyether type aspartate is used in two-component asparagus polyurea coatings, combining aliphatic polyaspartate and terminal amino polyether modified aliphatic isocyanate prepolymers to form a high-performance leading edge protective coating.

Benefits of technology

It realizes high-performance wind-sand and rain-fog corrosion resistance of wind-power blade leading edge protective coating, has excellent chemical resistance and mechanical mechanical properties, and has good construction performance, which is suitable for manual scraping and coating construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117887063B_ABST
    Figure CN117887063B_ABST
Patent Text Reader

Abstract

The present invention relates to coatings, and in particular to a polyether aspartic acid ester containing aldehyde (ketone) imine and application thereof in wind turbine blade coatings; the two-component aspartic polyurea coating ensures comprehensive and excellent material properties: as mentioned above, the compound of formula 1, as a macromolecular monomer having both a flexible segment and a ternary cross-linking function, gives comprehensive and excellent material properties that are difficult to obtain in ordinary two-component polyurea coatings, so that the aliphatic aspartic polyurea coating has the performance characteristics of a true elastomer, and well meets the performance requirements of wind turbine blade coatings including leading edge protection coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to coatings, in particular to a polyether aspartic acid ester containing aldehyde (ketone) imine and its application in wind turbine blade coatings Technical Background

[0002] Wind turbine blade coating is essentially an anti-corrosion protective coating for wind turbine blades. Its main function is to provide a smooth aerodynamic surface for wind turbine blades to prevent blades from being degraded by ultraviolet rays, eroded by moisture, and abraded by wind, sand, rain, and fog. Wind turbine blade coatings mainly resist two types of external erosion: the first is erosion from ultraviolet light; the second is erosion from wind, sand, rain, and fog. The former is chemical erosion, and the latter is mechanical erosion. In comparison, it is much more difficult to protect the latter than the former. This is because the wind power industry itself is still an emerging industry, and people's understanding of the erosion mechanism and prevention measures of wind, sand, rain, and fog on wind turbine blades is still immature, so there are still many problems that need to be solved.

[0003] Wind turbines are usually installed in wind-sand-rich areas, where the operating environment is harsh. The blades are subject to long-term friction from wind and impact erosion from sand, salt spray, and raindrops. In particular, the linear speed of the windward part of the leading edge of the blade tip is very high. For example, for a blade with a length of 70 meters, the linear speed of the leading edge can reach 80-90m / s (equivalent to 280-300km / h). It can be imagined that in such an environment, the impact damage of wind, sand, and raindrops on the leading edge of the blade is extremely serious. If the corrosion problem of the leading edge of the blade is not solved in time, it will not only affect the power generation efficiency, but also pose a hidden danger to the safety of the wind turbine when the blade is seriously damaged.

[0004] High-speed moving parts of industrial equipment, such as aircraft rotors and ship propellers, will also encounter strong erosion from wind, sand and fluids, but they can be maintained and serviced in a timely or regular manner. However, once wind turbines are in operation, their maintenance or service is extremely time-consuming, labor-intensive and expensive. Therefore, as a protective coating for wind turbine blades, especially the leading edge protective coating specially applied to the leading edge of the blade tip, in addition to having excellent chemical resistance, it must also have excellent resistance to wind, sand, rain and fog erosion.

[0005] As a special protective measure for the leading edge of the wind turbine blade, the leading edge protective coating is currently mostly applied by applying a leading edge protective film. This protective film is a PTU transparent film that needs to be applied manually, and the process requirements are very strict. However, despite this, blistering, edge curling, and weathering and displacement of the protective film at the blade tip often occur during the operation of the protective film. In the past decade, two-component wind turbine blade leading edge protective coatings have received attention and use in the industry, especially two-component polyurea coatings, which have received more and more attention, and there are many patent literature reports.

[0006] CN115678396 reports a two-component polyurea coating with low surface energy for wind turbine blades, which is mainly characterized by amino-terminated polyether and isocyanate modified by fluorinated polyether polyol. However, the amino-terminated polyether terminated with primary amino groups is too active, resulting in a too fast curing speed of the two-component gel, making it difficult to obtain a uniform and smooth protective coating on the surface of the wind turbine blade.

[0007] CN106068309 reports a two-component polyurea coating for wind turbine blades mainly characterized by polyaspartic acid ester and a certain specific ester. It is claimed that the specific ester in the polyurea coating composition can improve the coating's resistance to rain erosion and solid particle erosion. However, in one embodiment of the patent, the specific ester is an aromatic ester, which will have an adverse effect on the coating's aging resistance.

[0008] CN105992785 reports a two-component polyurea coating for wind turbine blades featuring polyaspartic acid ester and polycarbonate diol. However, the compatibility of polycarbonate diol and polyaspartic acid ester is not good, and more importantly, the reactivity of hydroxyl and amino groups with aliphatic isocyanate is very different, which makes their reaction speed with isocyanate curing agent asynchronous, affecting the cross-linking curing speed and degree of polycarbonate diol, and ultimately resulting in insufficient overall strength of the coating.

[0009] WO2020260578 reports a two-component polyurea coating specifically used for the leading edge protective coating of wind turbine blades. Its main feature is that the resin component is composed of a difunctional polyether polyaspartic acid ester or a mixture with an aliphatic polyaspartic acid ester. Compared with ordinary pure aliphatic aspartic polyurea, this difunctional polyether aspartic polyurea can significantly improve the elongation or viscoelasticity of the coating. However, as a leading edge protective coating, it is more necessary to have sufficient cohesive strength and elastic modulus, which cannot be met by this difunctional polyurea with a polyalkoxy ether structure.

[0010] CN115637100 reports a solvent-free, rain-resistant wind turbine blade coating, the main feature of which is to obtain a secondary amino complex with an aspartic acid ester structure by Michael addition of a mixture of a low molecular weight two-functional amino-terminated polyether and polytetramethylene ether glycol bis-p-aminobenzoate (P1000). The purpose of introducing P1000 in this patent is to improve the lack of rigidity of the two-functional amino-terminated polyether, but the aromatic groups at both ends of P1000 will affect the aging resistance of the coating.

[0011] As we all know, unlike the difunctional structure, the trifunctional amino-terminated polyether has the special function of promoting the aggregation and separation of the soft segment phase region and the hard segment phase region in the polymer cross-linking network, so it can significantly improve the resilience, tensile strength, tear strength and anti-friction performance of the polymer. However, ordinary trifunctional amino-terminated polyether contains three primary amino groups, and the reaction activity is extremely high. The general two-component construction process (such as air spraying, brushing, scraping, etc.) cannot be used at all. At the same time, the trifunctional amino-terminated polyether has three primary amino groups, and they cannot be converted into secondary amino groups through Michael addition like difunctional primary amino compounds to reduce the activity and facilitate use, because the steric hindrance space is too large when the three primary amino groups are added, and the reaction cannot be carried out to the end. Therefore, for many years, despite the many advantages of trifunctional amino-terminated polyether, it is often shelved due to the inconvenience of use in process performance.

[0012] WO2014151307 reports a method for preparing polyether aspartic acid esters using trifunctional amino-terminated polyethers. One of the methods provided by the patent is to simultaneously perform Michael addition on three primary amino groups with diethyl maleate, but the patent does not provide data on the conversion rate. The second method is to perform Michael addition on only one primary amino group with diethyl maleate, and the remaining two primary amino groups remain in the molecular structure. In fact, due to the large steric hindrance effect, it is difficult to convert all three primary amino groups in method one into secondary amino groups, and the remaining primary amino groups will still affect the reaction activity of the product. It can be seen that the patent cannot perform full secondary amination on trifunctional amino-terminated polyethers. On the other hand, in addition to a detailed description of the effect of different formulations on the drying speed of the coating, the patent does not mention the effect of trifunctional polyether aspartic acid esters on the performance of two-component aspartic polyurea coatings, and does not mention or suggest the application of trifunctional polyether aspartic acid esters in wind turbine blade coatings including leading edge protection coatings.

[0013] The above reports are not sufficient to solve the problems faced by wind turbine blade coatings. Summary of the invention

[0014] The purpose of this patent is to provide a trifunctional polyether aspartic acid ester structure and its synthesis method, and to use this resin in a two-component aspartic polyurea coating so that it can meet the actual use requirements of wind turbine blade coatings, especially leading edge protection coatings.

[0015] The present invention relates to an aldehyde (ketone) imine polyether aspartic acid ester having the following structural characteristics (Formula 1):

[0016]

[0017] Wherein R1 and R2 are C1-C4 alkyl groups, which may be the same or different; R3 is C1-C10 aliphatic alkyl group; R4 is hydrogen or C1-C10 aliphatic alkyl group; x, y and z are natural numbers of 1-5.

[0018] The present invention also relates to a method for synthesizing polyether aspartic acid ester (Formula 1) containing aldehyde (ketone) imine, which is characterized by:

[0019] 1. First, use an aldehyde (ketone) compound to block a primary amino group in the trifunctional amino-terminated polyether.

[0020] 2. Then, Michael addition reaction is carried out with unsaturated dicarboxylic acid ester.

[0021] The details are as follows: The synthesis method of the polyether aspartic acid ester containing aldehyde (ketone) imino group is divided into two steps:

[0022] In the first step, a small molecule aldehyde (ketone) compound is condensed with a trifunctional amino-terminated polyether to obtain an aldehyde (ketone) imine group, wherein the molar ratio of the aldehyde (ketone) compound to the amino-terminated polyether condensation reaction is 1:1. The reaction process is as follows:

[0023] As shown in formula 2:

[0024]

[0025] wherein R3, R4, x, y, and z are defined the same as above (Formula 1).

[0026] In the second step, the product in Formula 2 is subjected to Michael addition reaction with an unsaturated dicarboxylic acid ester to obtain a polyether aspartic acid ester containing an aldehyde (ketone) imino group, wherein the molar ratio of the addition of the product in Formula 2 to the unsaturated dicarboxylic acid ester is 1:2, and the reaction process is shown in Formula 3:

[0027]

[0028] wherein R1, R2, R3, R4 and x, y and z are defined the same as above (Formula 1).

[0029] In the first step, the condensation reaction of the small molecule aldehyde (ketone) compound and the trifunctional amino-terminated polyether can be carried out according to the common synthesis method of aldehyde (ketone) imine in the technical field, for example: firstly react the amino-terminated polyether with the aldehyde (ketone) compound at a temperature of 40-50°C for 2-3 hours, then raise the temperature to 80-90°C and reflux dehydrate with a water-carrying agent until the water output reaches the theoretical value, then raise the temperature to 90-110°C, remove the water-carrying agent by vacuum and cool to obtain the product of formula 2.

[0030] In the second step, the addition reaction of the product of formula 2 with the unsaturated dicarboxylic acid ester can be carried out according to the common method of Michael addition reaction in the technical field; for example, the unsaturated dicarboxylic acid ester is first slowly added dropwise to the product of formula 2, and the temperature is controlled within the range of 50-60° C. After the addition is completed, the temperature is raised to 60° C. and kept for reaction for 10-12 hours, and finally the temperature is raised to 100° C. and vacuumed for 1 hour to remove unreacted monomers, and the product of formula 3 is obtained after cooling, i.e., aldehyde (ketone)-containing imino polyether-type aspartic acid ester.

[0031] The trifunctional amino-terminated polyether can be a trifunctional amino-terminated polyether with a molecular weight of 200-800, preferably a molecular weight of 400, such as the commercially available amino-terminated polyether T-403.

[0032] The carbon-based small molecule aldehyde (ketone) compound includes, but is not limited to, acetaldehyde, propionaldehyde, butyraldehyde, isobutyraldehyde, acetone, butanone, 2-pentanone, 3-pentanone, 2-hexanone, 3-hexanone, 4-methyl-2-pentanone. Preferably, isobutyl ketone or 4-methyl-2-pentanone is used.

[0033] The unsaturated dicarboxylic acid esters may include but are not limited to dimethyl maleate, diethyl maleate, dibutyl maleate, dimethyl fumarate, diethyl fumarate and dibutyl fumarate, which may be used alone or in any proportion. Preferably, diethyl maleate is used.

[0034] The present invention relates to a two-component aspartic acid ester-containing aldehyde (ketone) imine polyether aspartic acid ester aspartic acid ester, which is characterized in that: the resin component and the curing agent component react together to form:

[0035] The resin component is composed of at least one aldehyde (ketone)-containing imino polyether type polyaspartic acid ester and at least one aliphatic polyaspartic acid ester.

[0036] Wherein: the aldehyde (ketone) imino polyether type polyaspartic acid ester has a structure as shown in Formula 1, and the aliphatic polyaspartic acid ester resin has a structure as shown in Formula 4:

[0037]

[0038] in:

[0039] R1, R2, R3, and R4 are C-C4 alkyl groups, which may be the same or different;

[0040] X: is the following structure (Formula 5):

[0041]

[0042] Or it can also be the following structure (Formula 6):

[0043]

[0044] Or it can also be the following structure (Formula 7):

[0045] CH2-CH2-CH2-CH2-CH2-CH2-CH2

[0046] Formula 7

[0047] Aliphatic polyaspartic acid ester products containing the structures of Formula 4, Formula 5, Formula 6 and Formula 7 are available on the market, such as AP-104, AP-105 and AP-102 from Weixin Paint.

[0048] As an optimization method, the composition (weight) ratio of the aldehyde (ketone) imine polyether type polyaspartic acid ester to the aliphatic polyaspartic acid ester is 1:9-9:1, preferably 2:8-5:5.

[0049] Curing agent component: composed of at least one aliphatic isocyanate prepolymer modified by amino-terminated polyether and at least one aliphatic isocyanate trimer;

[0050] Wherein: the amino-terminated polyether-modified aliphatic isocyanate prepolymer has the following structural formula (Formula 8):

[0051]

[0052] Wherein, x, y, z are natural numbers of 0-6 respectively; n is a natural number such as 1, 2, 3, 4, etc.; R is an aliphatic isocyanate alkylene group, and the aliphatic isocyanate includes but is not limited to isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), hydrogenated MDI (HMDI), and xylylene diisocyanate (XDI).

[0053] The amino-terminated polyether is a difunctional amino-terminated polyether with a molecular weight of 400-2000, and the preferred amount is 1000-2000. They can be used alone or mixed in any proportion.

[0054] The aliphatic isocyanate includes but is not limited to IPDI, HDI, HMDI and XDI, preferably IPDI and HMDI, which can be used alone or in any proportion.

[0055] The [NCO] / [HN] equivalent ratio of the reaction between the amino-terminated polyether and the aliphatic isocyanate is calculated as 2.0-5.0:1, preferably 3.5-4.5:1.

[0056] The synthesis of the amino-terminated polyether-modified aliphatic isocyanate prepolymer can be carried out as follows: first, slowly drop the amino-terminated polyether into the isocyanate in a cold water bath, and control the temperature not to exceed 30° C. After the dropwise addition is completed, the reaction is continued at low temperature for 1 hour, and then the temperature is raised to 60° C. to continue the reaction until the NCO% content reaches the designed value. The temperature is lowered to 40° C. and the material is discharged to obtain the product of formula 8, i.e., the amino-terminated polyether-modified aliphatic isocyanate prepolymer.

[0057] Aliphatic isocyanate trimer has the following structure (Formula 9):

[0058]

[0059] Wherein R is an alkylene group of HDI or IPDI.

[0060] The trimer of the aliphatic isocyanate includes IPDI trimer or HDI trimer, such as commercially available Covestro Desmodur N3300, N3600, N75, etc., preferably HDI trimer.

[0061] The curing agent component is composed of at least one amino-terminated polyether-modified aliphatic isocyanate prepolymer and at least one aliphatic isocyanate trimer, wherein the composition (weight) ratio of the amino-terminated polyether-modified aliphatic isocyanate prepolymer to the aliphatic isocyanate trimer is 4:6-9:1, preferably 6:4-8:2.

[0062] Further optimization methods:

[0063] As for the coating, the resin component, in addition to being composed of at least one aldehyde (keto) amino acid ester polyether aspartic acid resin and at least one aliphatic polyaspartic acid ester, can also add fillers, coupling agents, dispersants, thixotropic agents, pigments, leveling agents, defoaming agents, ultraviolet light absorbers and antioxidants as needed.

[0064] The filler can be calcium carbonate, talcum powder, titanium dioxide, silicon powder, barium sulfate, etc. They can be used alone or mixed in any proportion. The total amount of the filler used can account for 20-60% of the total weight of the resin component.

[0065] Preferred is 25-45%.

[0066] The coupling agent can be KH-550, KH-560, KH-602, etc. The amount of the coupling agent used is 0.1%-1% of the total weight of the pigment and filler in the resin component, preferably 0.1-0.5%.

[0067] The dispersant may be BYK-110, BYK-163, BYK-180, etc. The amount of the dispersant used is determined according to the supplier's recommendations.

[0068] The thixotropic agent can be fumed silica, kaolin, attapulgite, etc. The thixotropic agent can be used alone or mixed in any proportion. The total amount of the thixotropic agent used is 0-20%, preferably 0-15%.

[0069] The pigment can be carbon black, titanium dioxide, iron yellow, iron red, phthalocyanine blue, etc. The amount of pigment used depends on the color requirements of the coating.

[0070] The leveling agent can be BYK-333, BYK-354, etc. The leveling agent can be used alone or mixed in any proportion, and the amount used is determined according to the supplier's recommendation.

[0071] The defoamer can be BYK-066N, BYK-085, etc. The defoamer can be used alone or mixed in any proportion, and the amount used is determined according to the supplier's recommendation.

[0072] The ultraviolet light absorber can be 1130, 770 and 292, etc. The ultraviolet light absorber can be used alone or mixed in any proportion, and the amount used is determined according to the supplier's recommendation.

[0073] The antioxidants described can be 1010, B225 and 330, etc. The antioxidants can be used alone or mixed in any proportion, and the amount used is determined according to the supplier's recommendation.

[0074] The preparation method of the resin component in the two-component aspartic acid ester-containing aldehyde (ketone) imino polyether type aspartic acid ester can be carried out in the following order: 1. First, the aldehyde (ketone) imino polyether type polyaspartic acid ester and the aliphatic polyaspartic acid ester are weighed in proportion and mixed and stirred evenly in a container.

[0075] 2. Add measured coupling agent, dispersant, leveling agent, defoamer, UV absorber, antioxidant and other additives, and stir thoroughly.

[0076] 3. Add filler, thixotropic agent and color paste and stir thoroughly, then increase the stirring speed (2000rpm) and disperse at high speed for 30 minutes to obtain the resin component.

[0077] In the curing agent component, in addition to at least one amino-terminated polyether-modified aliphatic isocyanate prepolymer and at least one aliphatic isocyanate trimer, an appropriate amount of reactive diluent and plasticizer may be added according to the viscosity requirements, wherein the reactive diluent may be propylene carbonate, γ-butyrolactone, etc., and the plasticizer may be dioctyl phthalate, acetyl tributyl citrate, etc. They may be used alone or mixed in any proportion.

[0078] The preparation method of the curing agent component can be carried out in the following order:

[0079] 1 First, weigh a measured amount of amino-terminated polyether-modified aliphatic isocyanate prepolymer and pour it into a container.

[0080] 2. Add measured active diluent or plasticizer and stir evenly.

[0081] 3. Add the measured amount of isocyanate trimer and stir evenly to obtain the curing agent component.

[0082] The two-component aspartic acid ester-containing aldehyde (ketone) imine polyether aspartic acid ester used for the leading edge protection coating of wind turbine blades involved in the present invention is a solvent-free system, suitable for manual scraping and construction, and the scraping area is on both sides of the windward part of one-third of the length of the tip of the wind turbine blade. The viscosity of the A (resin) component and the B (curing agent) component of the coating are 5000-6000mPa.s and 25000-55000mPa.s respectively, and the (weight) mixing ratio of the two components is A:B=1:1.0-1.6.

[0083] The specific construction methods and requirements are as follows:

[0084] 1 Weigh components A and B according to the mixing ratio.

[0085] 2. Mix components A and B and stir thoroughly with a painter's knife, and try to avoid air bubbles being trapped in the material.

[0086] 3. Apply the paint evenly on the cleaned area to be painted, and control the wet thickness between 150-200μm. Wait for 60 minutes for the wet film to dry and form before applying the second coat of paint. The mixed paint must be used within 1 hour.

[0087] 4 Repeat steps 1 and 2, apply the second coat after the first coat, control the wet film thickness between 150-200μm (to ensure the total dry film thickness is greater than 300μm), and keep the coating surface uniform, smooth and flawless. The mixed paint must be used within 1 hour.

[0088] 5. At ambient temperature, the coating will be completely cured after two hours in summer and the blades can be moved. In winter, it takes 3 hours for the coating to be completely cured and the blades can be moved.

[0089] Innovation

[0090] 1. The first innovation of the present invention is to first use a small molecule aldehyde (ketone) compound to block a primary amino group in the trifunctional amino-terminated polyether, thereby reducing the steric hindrance space for the subsequent Michael addition reaction, thereby successfully obtaining a polyether-type aspartic acid ester with controllable reaction activity and trifunctionality, that is, the compound of formula 1.

[0091] 2. The second innovation of the present invention is to apply the compound of formula 1 to two-component asparagine polyurea coating.

[0092] 3. The third innovation of the present invention is to introduce a difunctional amino-terminated polyether into aliphatic isocyanate prepolymer. In the current polyurethane / polyurea technology field, in order to improve the crosslinking performance of the curing agent, polyesters containing hydroxyl groups, tetrahydrofuran polyethers or polycarbonate diols are usually used as the soft segment of the curing agent, but what is obtained is essentially a carbamate-modified curing agent. The present invention uses amino-terminated polyether as the soft segment to obtain a urea-modified curing agent, so that all crosslinking points in the polymer crosslinking network are completely composed of urea bonds, which maximizes the phase separation of the hard segment phase region and the soft satin phase region and improves the elastomeric properties of the polymer coating.

[0093] Beneficial effects:

[0094] 1. Comprehensive and excellent material performance: The leading edge protection coating specially applied to the leading edge of the blade tip, in addition to having excellent chemical resistance, must also have sufficiently long-term excellent resistance to wind and sand, rain and fog erosion. Therefore, wind turbine blade coatings are different from ordinary coatings. They require extremely strict corrosion resistance, such as resistance to moisture and heat (2000hr), aging resistance (2500hr), and salt spray resistance (2000hr). At the same time, they also require extremely strict mechanical properties, such as rain erosion resistance (>20hr), elongation at break (>300%), wear resistance (<60mg), etc., so special raw material components and formulas are required. Based on the above three innovative points, the aldehyde (ketone) imine polyether type asparagine polyurea coating of the present invention not only meets the above corrosion resistance requirements, but also has the performance characteristics of a true elastomer, that is, the ability to fully absorb high-speed impacts such as wind and sand, raindrops, etc., thereby well meeting the performance requirements of wind turbine blade coatings including leading edge protection coatings.

[0095] 2. Convenient and practical construction performance: The curing reaction process of the two-component coating is as follows: First, the two secondary amino groups of Formula 1 react with the isocyanate group. The reaction activity of this step is equivalent to that of ordinary aliphatic polyaspartic acid esters, and the speed is controllable. Then the aldehyde (ketone) imine of Formula 1 releases the primary amino group after absorbing moisture in the air, and the primary amino group reacts quickly with the isocyanate. At this time, the aldehyde (ketone) imine plays a role of latent catalysis and curing, so that the curing speed of this two-component polyurea system can be comparable to that of ordinary two-component polyurethane or aspartic polyurea system. Such process characteristics can be used for both mechanical spraying and manual brushing and scraping. BRIEF DESCRIPTION OF THE DRAWINGS

[0096] Figure 1 Infrared spectrum of the product of the first step of Example 1;

[0097] Figure 2Infrared spectrum of the product of the second step of Example 1;

[0098] Figure 3 Infrared spectrum of the product of the first step of Example 2;

[0099] Figure 4 Infrared spectrum of the product of the second step of Example 2. DETAILED DESCRIPTION

[0100] The main raw materials used in this example are listed in Table 1.

[0101] Table 1 List of main raw material information

[0102] Serial number Product Name Code supplier 1 Trifunctional amino-terminated polyether T-403 Yangzhou Chenhua 2 Difunctional amino-terminated polyether D-2000 Yangzhou Chenhua 3 Difunctional amino-terminated polyether D-1000 Yangzhou Chenhua 4 Isobutyraldehyde IBA Commercially available chemical reagents 5 4-Methyl-2-pentanone MIBK Commercially available chemical reagents 6 Diethyl Maleate DM Shanghai Gaoming Chemical Co., Ltd. 7 Aliphatic diisocyanate HMDI Covestro 8 HDI trimer 3300 Covestro 9 Aliphatic polyaspartic acid ester AP-104 Weixin Paint 10 Aliphatic polyaspartic acid ester AP-105 Weixin Paint 11 Polyether polyaspartic acid ester 2000S Weixin Paint

[0103] Example 1 Preparation of polyether aspartic acid ester containing aldimine

[0104] first step

[0105] Add 400 g (1 mol) of T-403 and 250 g of cyclohexane to a 2000 ml four-necked flask equipped with a stirrer, a thermometer, a nitrogen conduit, a reflux tube and a constant pressure dropping funnel. Use vacuum to replace the air in the flask with nitrogen and keep the nitrogen flowing. Turn on the stirrer and slowly add 72.1 g (1 mol) of IBA through the constant pressure funnel. Use a cold water bath to control the temperature of the reactants in the flask within the range of 25-35°C, and control the dropping time to about 1 hour. After the addition is complete, heat to 50°C and keep warm for 3 hours. Then install an oil-water separator under the reflux tube and heat to 90°C. Reflux to separate the water until the water output reaches the theoretical value. Heat to 100°C again and remove cyclohexane under vacuum. Cool to room temperature and set aside. See Appendix for infrared spectrum Figure 1 .

[0106] Depend on Figure 1 It can be seen that at 1668.12cm -1 A very obvious aldimine-C=N characteristic peak appeared at 1731cm -1 The carbonyl -C=O peak nearby has completely disappeared, and the 1106.94 cm -1 The nearby peak is the stretching vibration peak of the carbon-oxygen ether bond -COC-. Based on this, it can be shown that the aldimine substance was synthesized from T-403 and IBM.

[0107] Step 2

[0108] Start stirring and nitrogen, and continue to slowly add 344.4 grams (2 mol) of DM to the product of the first step, control the material temperature between 50-60°C, and control the dripping speed so that DM drips in about 1 hour. Then keep the temperature at 60°C for 10-18 hours, and cool to room temperature to obtain polyether aspartic acid ester containing aldimine, marked as AEA-400. The theoretically calculated amino equivalent is 272, and the infrared spectrum is shown in the appendix Figure 2 .

[0109] from Figure 2 It can be found that at 1644cm -1 The characteristic peak of the double bond -C=C of DM at has completely disappeared, which indicates that the remaining primary amino groups of T-403 have completely reacted with DM and converted into secondary amino groups.

[0110] Example 2 Preparation of polyether aspartic acid ester containing ketimine

[0111] first step

[0112] Add 400 g (1 mol) of T-403 and 250 g of cyclohexane to a 2000 ml four-necked flask equipped with a stirrer, a thermometer, a nitrogen conduit, a reflux tube and a constant pressure dropping funnel. Use vacuum to replace the air in the flask with nitrogen and keep the nitrogen flowing. Turn on the stirrer and slowly add 100.2 g (1 mol) of MIBK through the constant pressure funnel. Use a cold water bath to control the temperature of the reactants in the flask within the range of 25-35°C, and control the dropping time to about 1 hour. After the addition is complete, heat to 50°C and keep warm for 3 hours. Then install an oil-water separator under the reflux tube and heat to 90°C. Reflux to separate the water until the water output reaches the theoretical value. Heat to 100°C again and remove cyclohexane under vacuum. Cool to room temperature and set aside. See Appendix for infrared spectrum Figure 3 .

[0113] Depend on Figure 3 It can be seen that at 1658.48cm -1 A very obvious ketimine-C=N characteristic peak appeared at 1731cm -1 The carbonyl -C=O peak nearby has basically disappeared, and the 1105.01cm -1 The nearby peak is the stretching vibration peak of the carbon-oxygen ether bond -COC-. Based on this, it can be shown that ketimine substances are synthesized from T-403 and MIBK.

[0114] Step 2

[0115] Start stirring and nitrogen, and continue to slowly add 344.4 grams (2 mol) of DM to the product of the first step, control the material temperature between 50-60°C, and control the dripping speed so that DM drips in about 1 hour. Then keep the temperature at 60°C for 10-12 hours, and cool to room temperature to obtain a polyether aspartic acid ester containing ketimine, marked as KEA-400. The theoretically calculated amino equivalent is 282. See the appendix for the infrared spectrum Figure 4 .

[0116] from Figure 4 It can be found that at 1644cm -1 The characteristic peak of the double bond -C=C of DM at has completely disappeared, which indicates that the remaining primary amino groups of T-403 have completely reacted with DM and converted into secondary amino groups.

[0117] Example 3 Preparation of amino-terminated polyether-modified aliphatic isocyanate prepolymer

[0118] 262.3 g (1 mol) of HMDI was added to a 1000 ml four-necked flask equipped with stirring, a thermometer, a nitrogen conduit, a reflux tube and a constant pressure dropping funnel. The air in the flask was replaced with nitrogen by vacuum and kept flowing with nitrogen. Stirring was started and 513.9 g (0.26 mol) of D-2000 was slowly added dropwise through a constant pressure funnel. The temperature of the reactants in the flask was controlled within the range of 25-35°C with a cold water bath, and the dropping time was controlled within about 1 hour. After the dropwise addition was completed, the reaction was maintained at 40°C for 1 hour, and then the temperature was raised to 60°C for about 2 hours until the NCO% content reached 8.0%. The amino-terminated polyether-modified aliphatic isocyanate prepolymer was obtained by cooling to 40°C, and the viscosity was measured to be 30117 mPa·s.

[0119] Example 4 Preparation of amino-terminated polyether-modified aliphatic isocyanate prepolymer

[0120] 262.3 grams (1 mol) of HMDI were added to a 1000ml four-necked flask equipped with stirring, a thermometer, a nitrogen conduit, a reflux line and a constant pressure dropping funnel. The air in the flask was replaced with nitrogen by vacuum and nitrogen was kept flowing. Stirring was turned on and 326 grams (0.16 mol) of D-2000 were slowly added dropwise through a constant pressure funnel. The reactant temperature in the flask was controlled within the range of 25-35°C with a cold water bath, and the dropping time was controlled to about 1 hour. After completion of the dropwise addition, the reaction was carried out at 35°C for 1 hour. Then 139.7 grams (0.14 mol) of D-1000 were added dropwise, the temperature was controlled within the range of 25-35°C, the dropping time was controlled to about 0.5, and the temperature was raised to 40°C and the constant temperature reaction was carried out for 1 hour after the dropwise addition was completed, and then the temperature was raised to 60°C and the reaction was carried out for about 2 hours, until the NCO% content reached 8.0%. The solution was cooled to 40°C to obtain an amino-terminated polyether-modified aliphatic isocyanate prepolymer, and the viscosity was measured to be 10291 mPa·s.

[0121] Example 5 Preparation of two-component polyurea coating resin component A1 containing aldimine polyether aspartic acid ester 1 First, mix the raw material components of A1 formula No. 3-9 in Table 2 evenly, and disperse at high speed (>2000rpm) for 20min. 2 Then, add the raw material components No. 10-15 to the mixed solution in sequence, stir well and grind with a sand mill to a fineness of ≤25μm to obtain a gray color paste containing resin components.

[0122] 3 Then, the raw material components No. 1-2 and 16-19 were added to the gray paste in sequence, and the mixture was dispersed at high speed (2000 rpm) for 30 minutes to obtain resin component A1, and the viscosity was measured to be 2927 mPa·s.

[0123] Example 6 Preparation of two-component polyurea coating resin component A2 containing ketimine polyether aspartic acid ester According to the formula of A2 in Table 2, the complete process of Example 5 was followed to obtain resin component A2.

[0124] Example 7 Preparation of two-component polyurea coating resin component A3 containing aldehyde and ketimine polyether aspartic acid ester According to the formula of A3 in Table 2, the complete process of Example 5 was followed to obtain resin component A3.

[0125] Example 8 Preparation of two-component polyurea coating resin component A4 containing aldimine polyether aspartic acid ester According to the formula of A4 in Table 2, the complete process of Example 5 was followed to obtain resin component A4.

[0126] Example 9 Preparation of two-component polyurea coating resin component A5 containing ketimine polyether aspartic acid ester According to the formula of A5 in Table 2, the complete process of Example 5 was followed to obtain resin component A5.

[0127] Example 10 Preparation of curing agent component B1 of two-component polyurea coating containing aldehyde (ketone) imine polyether aspartic acid ester 1 Weigh 8 parts of the amino-terminated polyether-modified aliphatic isocyanate prepolymer obtained in Example 3.

[0128] 2 Weigh 2 parts of HDI trimer 3300.

[0129] 3. Mix the two evenly to obtain curing agent component B1. The average viscosity was measured to be 35348 mPa·s and the average NCO content was 10.6%.

[0130] Example 11 Preparation of curing agent component B2 of two-component polyurea coating containing aldehyde (ketone) imine polyether aspartic acid ester 1 Weigh 8 parts of the amino-terminated polyether-modified aliphatic isocyanate prepolymer obtained in Example 4.

[0131] 2 Weigh 2 parts of HDI trimer 3300.

[0132] 3. Mix the two evenly to obtain curing agent component B2. The average viscosity was measured to be 13472 mPa·s and the average NCO content was 10.6%.

[0133] Example 12 Preparation of two-component coating test piece F1

[0134] 1 Prepare the glass fiber reinforced epoxy composite test board (FR4) in advance with the specification of 75×150×10mm. Use putty to repair and fill the base surface before painting, and then polish it flat for standby use.

[0135] Prepare the test piece steel mold in advance with specifications of 200×200×2mm, clean it, apply mold release agent and set aside for use.

[0136] 2 Weigh components A1 and B1 according to the formula ratio of F1 in Table 3, stir and mix thoroughly to avoid cavitation.

[0137] 3. Apply the mixed coating on the glass fiber reinforced epoxy resin composite board in 2-3 times, with an interval of 60 minutes between each application, until the cumulative thickness of the coating reaches more than 300μm. Ensure that the coating surface is flat and smooth.

[0138] 4. Scrape the mixed coating on the test piece steel mold until the wet film thickness reaches 2mm. Ensure that the coating surface is flat and smooth and there are no bubbles in the film. 5. Place the coated film until it is completely cured to obtain the coating test piece F1. Continue to place it for 7 days and then test the performance.

[0139] Example 13-Example 17 Preparation of two-component coating test pieces F2-F6

[0140] According to the formula ratio of F2-F6 in Table 3, the corresponding A and B components are weighed, and then the complete process of Example 12 is followed to obtain coating test pieces F2-F6.

[0141] Comparative Example 1 Preparation of aliphatic isocyanate prepolymer modified with polycarbonate diol

[0142] 262.3 g (1 mol) of HMDI was added to a 1000 ml four-necked flask equipped with stirring, a thermometer, a nitrogen conduit, a reflux tube and a constant pressure dropping funnel. The air in the flask was replaced with nitrogen by vacuum and kept flowing with nitrogen. Stirring was started and 513.9 g (0.26 mol) of PCDL-2000 was slowly added dropwise through the constant pressure funnel. The temperature of the reactants in the flask was controlled within the range of 25-35°C with a cold water bath, and the dropping time was controlled within about 1 hour. After the dropwise addition was completed, the reaction was maintained at 40°C for 1 hour, and then the temperature was raised to 60°C for about 2 hours until the NCO% content reached 8.0%. The polycarbonate diol-modified aliphatic isocyanate prepolymer was obtained by cooling to 40°C, and the viscosity was measured to be 20640 mPa·s.

[0143] Comparative Example 2 Preparation of Comparative Example Resin Component AC1 According to the formula of AC1 in Table 2, the complete process of Example 5 was followed to obtain resin component AC1.

[0144] Comparative Example 3 Preparation of Comparative Example Resin Component AC2 According to the formula of AC2 in Table 2, the complete process of Example 5 was followed to obtain resin component AC2.

[0145] Comparative Example 4 Comparative Example Curing Agent Component BC1

[0146] 1 Weigh 8 parts of the polycarbonate diol-modified aliphatic isocyanate prepolymer obtained in Comparative Example 1.

[0147] 2 Weigh 2 parts of HDI trimer 3300.

[0148] 3. The above three materials were mixed evenly to obtain the comparative curing agent BC1 component. The average viscosity was measured to be 16000 mPa·s and the average NCO content was 8.8%.

[0149] Comparative Example 5-Comparative Example 7 Preparation of Coating Test Pieces FC1-FC3

[0150] According to the formula ratio of FC1-FC3 in Table 3, the corresponding A and B components are weighed, and then the complete process of Example 12 is followed to obtain comparative coating test pieces FC1-FC3.

[0151] Table 2 is a comparison of the formulations of the resin components in Examples 5-8 and Comparative Examples 2-3, and each component is calculated by weight.

[0152] Table 2 List of formulations of component A with different formulations

[0153]

[0154]

[0155] Table 3 shows the proportions of the coatings composed of the resin components A1-A5, AC1-AC2 and the curing agent components B1, B2 and BC1, as well as their main performance test results. Each corresponding coating is represented by F1-F6 and FC1-FC3. Each component is measured in weight units.

[0156] Table 3 List of coating compositions and main properties in various embodiments and comparative examples

[0157]

[0158]

[0159] Note*: Quoted from the enterprise standard of a domestic wind turbine blade manufacturer

[0160] From the results shown in Table 3, it can be seen that only the coating obtained by the present invention can meet the corresponding technical requirements, while the comparative example cannot meet the corresponding requirements.

Claims

1. An aldehyde or ketimine-containing polyether aspartic acid ester having the following structure as shown in Formula I: Wherein R1 and R2 are C1-C4 alkyl groups, which may be the same or different; R3 is C1-C10 aliphatic alkyl group; R4 is hydrogen or C1-C10 aliphatic alkyl group; x, y and z are natural numbers of 1-5.

2. The method for synthesizing polyether aspartic acid ester containing aldehyde or ketimine according to claim 1, characterized in that: Follow these steps to achieve this: In the first step, a small molecule aldehyde or ketone compound is condensed with a trifunctional amino-terminated polyether to obtain an aldehyde or ketimine group, wherein the molar ratio of the aldehyde or ketone compound to the amino-terminated polyether condensation reaction is 1:1, and the reaction process is shown in Formula 2: In the second step, the product of Formula 2 is subjected to Michael addition reaction with an unsaturated dicarboxylic acid ester to obtain a polyether aspartic acid ester containing an aldehyde or ketone imino group, wherein the molar ratio of the addition of the product of Formula 2 to the unsaturated dicarboxylic acid ester is 1:2, and the reaction process is shown in Formula 3: Wherein R1 and R2 are C1-C4 alkyl groups, which are the same or different; R3 is C1-C10 aliphatic alkyl group; R4 is hydrogen or C1-C10 aliphatic alkyl group; x, y and z are natural numbers of 1-5.

3. The method for synthesizing polyether aspartic acid ester containing aldehyde or ketimine according to claim 1, characterized in that: In the first step, the trifunctional amino-terminated polyether is reacted with an aldehyde or ketone compound at a temperature of 40-50° C. for 2-3 hours, and then the temperature is raised to 80-90° C. and dehydrated by reflux with a water-carrying agent until the water output reaches the theoretical value, and then the temperature is raised to 90-110° C., and the water-carrying agent is removed by vacuum and then cooled to obtain the product of formula 2; In the second step, the unsaturated dicarboxylic acid ester is first slowly added dropwise to the product of formula 2, and the temperature is controlled within the range of 50-60° C.; after the addition is completed, the temperature is raised to 60° C. for insulation reaction for 10-12 hours, and finally the temperature is raised to 100° C. for 1 hour to remove unreacted monomers, and the product of formula 3 is obtained after cooling, i.e., aldehyde- or ketone-containing imino polyether-type aspartic acid ester; The trifunctional amino-terminated polyether is a trifunctional amino-terminated polyether with a molecular weight of 200-800; the carbon-based small molecule aldehyde or ketone compound includes acetaldehyde, propionaldehyde, butyraldehyde, isobutyraldehyde, acetone, butanone, 2-pentanone, 3-pentanone, 2-hexanone, 3-hexanone, etc., 4-methyl-2-pentanone; The unsaturated dicarboxylic acid esters include dimethyl maleate, diethyl maleate, dibutyl maleate, dimethyl fumarate, diethyl fumarate and dibutyl fumarate, which can be used alone or in any proportion.

4. A two-component aspartic acid ester-containing aldehyde or ketimine polyether aspartic acid ester aspartic acid ester, characterized in that: Including resin component and curing agent component: (1) A resin component comprising at least one aldehyde- or ketone-containing imino polyether type polyaspartic acid ester as claimed in claim 1 or 2 and at least one aliphatic polyaspartic acid ester; Wherein: the aldehyde or ketone imino polyether type polyaspartic acid ester has a structure as shown in Formula 1, and the aliphatic polyaspartic acid ester resin has a structure as shown in Formula 4: in: R1, R2, R3, and R4 are C-C4 alkyl groups, which may be the same or different; X: is formula 5: Or formula 6: Or formula 7: -CH2-CH2-CH2-CH2-C212 Formula 7 The weight ratio of the aldehyde or ketimine polyether type polyaspartic acid ester to the aliphatic polyaspartic acid ester is 1:9-9:1; (2) a curing agent component: composed of at least one amino-terminated polyether-modified aliphatic isocyanate prepolymer and at least one aliphatic isocyanate trimer; Wherein: the amino-terminated polyether-modified aliphatic isocyanate prepolymer has a structure shown in Formula 8: Wherein, x, y, z are natural numbers of 0-6 respectively; n is a natural number of 1, 2, 3, 4, etc.; R is an aliphatic isocyanate alkylene group; The amino-terminated polyether-modified aliphatic isocyanate prepolymer is obtained by the following steps: firstly slowly drop the amino-terminated polyether into the isocyanate in a cold water bath, and control the temperature not to exceed 30°C; after the dropwise addition is completed, continue the reaction at low temperature for 1 hour, then heat up to 60°C and continue the reaction until the NCO% content reaches the designed value; cool down to 40°C and discharge to obtain the product of formula 8, i.e., the amino-terminated polyether-modified aliphatic isocyanate prepolymer; wherein the [NCO] / [HN] equivalent ratio of the amino-terminated polyether and the aliphatic isocyanate reaction is 2.0-5.0:1, the amino-terminated polyether is a two-functional amino-terminated polyether with a molecular weight of 400-2000, which is used alone or mixed in any proportion; the aliphatic isocyanate includes IPDI, HDI, HMDI and XDI, which are used alone or mixed in any proportion; The aliphatic isocyanate trimer has the structure shown in Formula 9 wherein R is an alkylene group of HDI or IPDI; The weight ratio of the amino-terminated polyether-modified aliphatic isocyanate prepolymer to the aliphatic isocyanate trimer is 4:6-9:

1.

5. A two-component aspartic acid ester-containing aldehyde or ketimine polyether aspartic acid ester according to claim 4, characterized in that: (1) The resin component described above, in addition to at least one aldehyde- or ketoamine-ester polyether-type aspartic acid resin and at least one aliphatic polyaspartic acid ester, may further contain fillers, coupling agents, dispersants, thixotropic agents, pigments, leveling agents, defoamers, ultraviolet light absorbers and antioxidants as needed; (2) In the curing agent component, in addition to at least one amino-terminated polyether-modified aliphatic isocyanate prepolymer and at least one aliphatic isocyanate trimer, appropriate amounts of reactive diluent and plasticizer may be added according to viscosity requirements.

6. A two-component aspartic acid ester-containing aldehyde or ketimine polyether aspartic acid ester according to claim 5, characterized in that: (1) In the resin component, The filler is calcium carbonate, talcum powder, titanium dioxide, silicon powder, barium sulfate, which are used alone or mixed in any proportion, and the total amount of the filler accounts for 20-60% of the total weight of the resin component; The coupling agent is KH-550, KH-560 or KH-602, and the amount of the coupling agent used is 0.1%-1% of the total weight of the pigment and filler in the resin component; The dispersant is BYK-110, BYK-163 or BYK-180; The thixotropic agent can be fumed silica, kaolin or attapulgite, which can be used alone or mixed in any proportion, and the amount of the thixotropic agent used accounts for 0-20% of the total weight of the resin component; The pigment is carbon black, titanium dioxide, iron yellow, iron red or phthalocyanine blue; The leveling agent is BYK-333 or BYK-354; the leveling agent is used alone or mixed in any proportion; The defoamer is BYK-066N or BYK-085, and the defoamer is used alone or mixed in any proportion; The ultraviolet light absorber is 1130, 770 or 292, and the ultraviolet light absorber is used alone or mixed in any proportion; The antioxidant is 1010, B225 or 330; the antioxidant is used alone or mixed in any proportion; (2) In the curing agent component The active diluent is propylene carbonate or gamma-butyrolactone, which can be used alone or in any proportion; the plasticizer is dioctyl phthalate or acetyl tributyl citrate, which can be used alone or in any proportion.

7. A two-component aspartic acid ester-containing aldehyde or ketimine polyether aspartic acid ester according to claim 5 or 6, characterized in that: (1) The preparation method of the resin component can be obtained according to the following steps: Firstly, aldehyde- or ketone-containing imino polyether type polyaspartic acid ester and aliphatic polyaspartic acid ester are weighed in proportion and mixed and stirred evenly in a container; Secondly, add the measured coupling agent, dispersant, leveling agent, defoamer, UV absorber and antioxidant, and stir well; Finally, add filler, thixotropic agent and color paste and stir well, then increase the stirring speed to 2000 rpm and disperse at high speed for 30 minutes to obtain the resin component; (2) The preparation method of the curing agent component can be carried out in the following order: Firstly, weigh a measured amount of amino-terminated polyether-modified aliphatic isocyanate prepolymer and pour it into a container; Secondly, add the measured active diluent or plasticizer and stir evenly; Finally, add the measured amount of isocyanate trimer and stir evenly to obtain the curing agent component.

8. A two-component aspartic acid ester-containing aldehyde or ketimine polyether aspartic acid ester according to any one of claims 4 to 6, characterized in that: The viscosity of the resin component is 5000-6000 mPa.s, the viscosity of the curing agent component is 25000-55000 mPa.s, and the mixing weight ratio of the resin component to the curing agent component is 1:1.0-1.

6.

9. The use of a two-component aspartic acid ester-containing aldehyde or ketimine polyether aspartic acid ester as claimed in claim 8 on a wind turbine blade, characterized in that: Step 1, weighing the resin component and the curing agent component according to the mixing ratio; Step 2, mix the resin component and the curing agent component and stir them thoroughly; Step 3: Apply the paint evenly on the cleaned area to be painted, and control the wet thickness between 150-200μm; wait for 60 minutes for the wet film to dry and form initially before applying the second coat of paint; the mixed paint must be used within 1 hour; Step 4: Repeat steps 1 and 2, apply the second coat on top of the first coat, control the wet film thickness between 150-200μm, ensure that the total dry film thickness is greater than 300μm, and keep the coating surface uniform, smooth and flawless; the mixed paint must be used within 1 hour; Step 5: At ambient temperature, the coating will be completely cured after two hours in summer and the blades can be moved; it takes three hours in winter for the coating to be completely cured and the blades can be moved.

Citation Information

Patent Citations

  • Polyaspartic coating compositions

    WO2014151307A1

  • Use of coating compositions for wind turbine blades

    WO2020260578A1

  • Modified asparaginic acid ester resin containing imino group as well as preparation method and application of modified asparaginic acid ester resin

    CN116606218A

  • Imide modified asparaginic acid ester resin as well as preparation method and application thereof

    CN116606413A